Engineering the interactions and dynamics of ultracold atom gases - Zhou, Yijia (2021)
Ultracold atoms are used to study various fundamental physics, including many-body system, nonequilibrium dynamics, and find many applications in quantum computing and quantum sensing. In this thesis, we studied the dynamics of ultracold atom gases with controllable two-body interactions. One of the major concerns is to manipulate the atomic states with electromagnetic fields. Here, we will show four projects associated with this topic.